2023
DOI: 10.1177/08919887231195219
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden in Parkinson Disease: A Scoping Review of the Literature from 2017-2022

Whitley W. Aamodt,
Benzi M. Kluger,
Miray Mirham
et al.

Abstract: Caregiver burden is a term that refers to the adverse effect of caregiving on the physical, emotional, social, spiritual, and financial well-being of the caregiver. Caregiver burden is associated with providing care to an individual with a chronic illness or disability, and the unique symptoms of Parkinson disease (PD) can amplify a patient’s needs and reliance on others, leading to adverse outcomes for patients and their caregivers. In this scoping review of the literature from January 2017 through April 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 128 publications
(222 reference statements)
0
2
0
Order By: Relevance
“…Although we could not determine the exact reasons for readmission in our cohort, other studies have demonstrated that readmissions among PD patients are associated with medical comorbidities, elective surgeries, and caregiver strain ( Shahgholi et al, 2017 ; Fullard et al, 2020 ). For example, persons with advanced PD become increasingly reliant on caregivers for support, and increasing physical dependence can lead to caregiver burden ( Lo Monaco et al, 2021 ; Aamodt et al, 2023b ). Caregiver burden and depression are associated with a higher risk of emergency department visits ( Rashid et al, 2023 ) and re-hospitalization among persons with PD ( Shahgholi et al, 2017 ), presumably when caregivers are overwhelmed and require additional support.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not determine the exact reasons for readmission in our cohort, other studies have demonstrated that readmissions among PD patients are associated with medical comorbidities, elective surgeries, and caregiver strain ( Shahgholi et al, 2017 ; Fullard et al, 2020 ). For example, persons with advanced PD become increasingly reliant on caregivers for support, and increasing physical dependence can lead to caregiver burden ( Lo Monaco et al, 2021 ; Aamodt et al, 2023b ). Caregiver burden and depression are associated with a higher risk of emergency department visits ( Rashid et al, 2023 ) and re-hospitalization among persons with PD ( Shahgholi et al, 2017 ), presumably when caregivers are overwhelmed and require additional support.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings and awaiting the results of an ongoing validation study of the MNCD classification and of its application in a prospective follow‐up cohort, early observations suggest that the MNCD classification could be a useful tool to apply in PD patients to identify the main symptoms of the disease and to monitor the progression of the disorder. Neuropsychiatric symptoms, such as visual hallucinations, depression, cognitive impairment and/or dementia, falls, disability, and a more advanced stage disease, have been identified as patient factors associated with caregiver burden in PD (Aamodt et al., 2023 ). All these data are collected in the MNCD classification with also a proposed staging and scoring that indicates the degree of severity, from least to most.…”
Section: Introductionmentioning
confidence: 99%